Pengaruh saat Penggenangan dan Konsentrasi Nacl terhadap pertumbuhan dan Hasil serat tanaman Kenaf (Hibiscus cannabinus) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
A pot experiment was carried out to study the effect inundation dates and NaCI concentrations to the growth and yield of kenaf. The inundation was applied at 3,6 and 9 weeks after sowing (WAS), and NaC1 concentration were 0